ADDRESSING THE KEY ELEMENTS THAT SUPPORT SUCCESSFUL CLINICAL EXPERIENCE OF FINAL YEAR PRE-SERVICE TEACHERS - Saidin, Norshiha (UPI Press, 2011)
This paper explores final year pre-service teachers’ perceptions on the key elementscritical to support successful final year in-school clinical experience. The paper alsofocuses on how teacher education program helps prospective teachers move from beinga student to a professional able to take responsibility for others. The paper is an outcomeof a survey targeted to 104 TESL student teachers who had undergone 14 week guidedclinical experience in various schools in Malaysia. Additional qualitative data weregathered via a focus group interview. The key elements identified by student teachers forsuccessful school placement are effective communication especially in building positivepersonal and professional relationships with mentor teachers and supervisors. Concernswere also raised about the need to fulfill the needs of diverse groups of learners. Pre–service teachers also highlight the need to gain information related to their decision inteaching.Keyword: Pre-service clinical experience, teacher training, effective communication